Hybrid Project-based Instructional Model: Fostering Critical Thinking Skills and Creative Thinking Skills - Eli Trisnowati (Universitas Tidar, 2022)
Project-based learning is a learning approach that emphasizes students as learning actors who facilitate students to construct their knowledge. However, the application of project-based learning to learning at the tertiary level is a learning syntax that has not been designed by adjusting the characteristics of learning for the tertiary level. This study aims to analyze the effectiveness of case study-based learning conducted using a hybrid project-based learning model in improving students' critical thinking and creative thinking skills. This study used a non-equivalent control group research design with 70 samples divided into the experimental and control groups. The instruments used are standard critical thinking skills tests, namely Cornell Critical Thinking Test (CCTT) level X, creative thinking skills test instruments, and observation sheets. The results showed that hybrid project-based learning effectively improved students' critical and creative thinking skills. The increase in students' critical thinking skills is higher than students' creative thinking skills.